Improving Teachers 'Competence in Choosing Learning Models Through Academic Suvervision Activities in 173382 Huta Tinggi Private Vocational School, Parmonangan District, North Tapanuli District - Hutabarat, Hitda (Institute of Computer Science (IOCS), 2021)
This research was motivated by the weakness of teachers in choosing learning models in SD Negeri 173382 Huta Tinggi Kecamatan Parmonangan Kabupaten Tapanuli Utara. The purpose of this study is to improve teacher competency in choosing learning models. This type of research is School Action Research (PTS) which consists of two cycles. The results showed, in the first cycle, of the 5 aspects assessed, namely, conformity with the format of the assessment, the relevance of time with teaching materials, opening, core activities, and concluding scores averaged 65 percent 64.96% with sufficient categories. After repairs in the second cycle, the results of the average assessment of 7 teachers increased to 89 by 88.96% in the very good category. Based on the results of this study,